2013
DOI: 10.1086/668787
|View full text |Cite
|
Sign up to set email alerts
|

Silencing ofEcFLO, AFLORICAULA/LEAFYGene of the California Poppy (Eschscholzia californica), Affects Flower Specification in a Perigynous Flower Context

Abstract: Flowers are reproductive shoots produced by determinate floral meristems. The role of FLORICAULA/ LEAPY-like genes in the specification of flowers varies between lineages and has not been characterized in a basal eudicot species. Here we report the phenotypic effects of virus-induced silencing of EcFLO, a FLORICAULA/LEAFY homologue in the California poppy Eschscholzia californica. EcFLO silencing resulted in repeated sepal and petal whorl formation and internodes between calyxes. A subset of silenced flowers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“… All citations included in reference list of main article ( Bradley et al, 1996 ; Blázquez et al, 1997 ; Bradley et al, 1997 ; Kyozuka et al, 1998 ; Pnueli et al, 1998 ; Ratcliffe et al, 1999 ; Gourlay et al, 2000 ; Bomblies et al, 2003 ; Becker et al, 2005 ; Meng et al, 2007 ; Souer et al, 2008 ; Wreath et al, 2013 ). …”
Section: Additional Filesmentioning
confidence: 99%
“… All citations included in reference list of main article ( Bradley et al, 1996 ; Blázquez et al, 1997 ; Bradley et al, 1997 ; Kyozuka et al, 1998 ; Pnueli et al, 1998 ; Ratcliffe et al, 1999 ; Gourlay et al, 2000 ; Bomblies et al, 2003 ; Becker et al, 2005 ; Meng et al, 2007 ; Souer et al, 2008 ; Wreath et al, 2013 ). …”
Section: Additional Filesmentioning
confidence: 99%
“…Setting aside these caveats, it remains the case that none of our silenced phenotypes resemble the strong loss of FM identity that is observed in most core eudicot LFY or cymose UFO mutants. Notably, the Aquilegia phenotypes are reminiscent of what Wreath et al observed when they silenced EcFLO , a LFY ortholog in Eschscholzia californica (Wreath et al, 2013). Eschscholzia is a member of the Papaveraceae, which is deeply diverged from Aquilegia ’s family, the Ranunculaceae, within the order Ranunculales (Becker et al, 2005).…”
Section: Discussionmentioning
confidence: 76%
“…By contrast, in Aquilegia , aqlfy still retains substantial FM identity, so AqUFO function in stamen (and possibly petal) initiation could be independent of AqLFY . It is interestingly to note in this regard that EscFLO silencing in Eschscholzia also results in reduced organ number in some flowers, particularly the stamens (Wreath et al, 2013). This observation, combined with the fact that we see reduced AqLFY expression in the aqufo flowers and have confirmed the ability of AqLFY to interact with at least AqUFO1, makes us hesitant to assert that the organ loss phenotype is definitively independent of AqLFY .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, what we observed is that this structure originates from an intercalary meristem in the floral apex (Leins, 1972) and that during anthesis it preserves characteristics similar to those of surrounding organs such as the same indumentum of the sepals. Some ontogenetic processes can be controlled and shared by both sepal and hypanthium formation, since proper sepal development is necessary to initiate the perigynous hypanthium in Eschscholzia (Papaveraceae, Wreath et al, 2013).…”
Section: Discussionmentioning
confidence: 99%